ANTI-HYPERGLYCEMIC EFFECT OF KUNDRU (COCCINIA INDICA) ON PATIENTS OF DIABETES MELLITUS TYPE-2 (International Journal of Ayurveda and Pharma Research, 2020)
The disease Diabetes or Madhumeha is well documented in all perennial sources of Ayurvedic wisdom. The present study was done to evaluate the efficacy of Bimbi (Coccinia indica) in the patients of Diabetes mellitus type-2 through single blind study. Total 30 patients were selected and divided into two groups, 15 patients in each group i.e., A (Bimbi) & B (Barley). In this study it has been found that Madhumeha affects not only in elderly people but in adults too with slight female preponderance. The present study confirmed that after the treatment of 60 days, Bimbi (Coccinia indica) was found effective in treatment of Madhumeha and reduced majority of the symptoms of illness that including Prabootha mootrata (Excessive urination), Atitrushna (Excessive thirst), Avila mootrata (Turbid urine) and Dourbalya (Weakness). There was significant improvement in all the laboratory parameters in patients of Bimbi (Coccinia indica) treated group. The outcome showed that mean reduction in fasting blood sugar level was 19.86%, in PP blood sugar level was 24.52% and in HbA1c level was 8.4%.These outcomes suggest that the results of trial drug i.e., Coccinia indica (Bimbi) powder was highly significant at p-value